Deposits and Cutoff Ages of Horseshoe and Marion Oxbow Lakes, Red River, Manitoba - Brooks, Gregory; Medioli, Barbara (Géographie physique et Quaternaire, 2003)
AbstractHorseshoe Lake and the Marion Lake scar, along the Red River, southern Manitoba, were cored to investigate the timing of the meander cutoffs and the sedimentology of the channel in-fill deposits. The Horseshoe Lake core, 10.75 m long, consists of 9.73 m of silt-rich deposits inferred to be lacustrine from 0 to 4 m deep, transitional from 4 to 5 m deep and alluvial below 5 m deep. Four wood and charcoal specimens sampled from the core yielded radiocarbon ages of 310 ± 40, 1730 ± 50, 2040 ± 50 and 2240 ± 50 BP. The Marion Lake core, 16.77 m long, consists of 14.73 m of silt-rich deposits inferred to be lacustrine from 0 to 5 m deep and alluvial below 8.5 m deep; the transition is indistinct and falls between 5 to 8.5 m deep. Four wood samples from the fluvial deposits yielded radiocarbon ages of 1600 ± 40, 1700 ± 40, 1660 ± 40 and 1620 ± 40 BP. The cutoffs that led to the formation of Horseshoe and Marion lakes are interpreted to have occurred at ~1990 and ~1520 cal BP or shortly thereafter, respectively. The silt-rich, alluvial-lacustrine deposits in the lakes lack structural and textural characteristics that can be readily recognized in core to distinguish the depositional environments. The absence of coarse sediments at the base of the fluvial units at both sites implies that minor to negligible amounts of sand were transported along the thalwegs of the channels prior to the meanders being cutoff. The dominance of silt within the oxbow deposits reflects sediment supply as the geomorphic setting of the river is within an extensive glaciolacustrine clay plain.